Health care professionals’ attitudes, behaviours and barriers toward exercise promotion among patients: A systematic review - Pinar Avsar; Zena Moore; Husain Nasaif; Barry Moore; Declan Patton; Tom O’Connor; Vishnu Renjith (PLoS ONE, 2025)
Objective To determine health care professionals’ (HCPs) attitudes, behaviours, and barriers toward exercise promotion among patients. Method Using systematic review methodology, we included published studies focusing on health care professionals’ attitudes, behaviours, and barriers towards exercise promotion among patients. The search was conducted in June 2023, using the Cochrane Central Register of Controlled Trials (CENTRAL), PubMed/MEDLINE, Embase, Cumulative Index to Nursing and Allied Health Literature (CINAHL) Plus, and Scopus databases, and returned 352 records, of which 34 met the inclusion criteria. The Critical Appraisal Skills Programme (CASP) tool was used for quality appraisal. Results Results revealed that HCPs hold a positive attitude towards advocating physical activity. Further physical activity was prescribed to achieve a number of objectives, including enhancing physical function, encouraging an active lifestyle, preventing complications, monitoring progress or compliance, and preventing functional decline. Barriers to exercise promotion identified related to four overarching categories: health professional-based barriers, perceived patient-related barriers, organisational barriers and health system-related barriers. Conclusion This review highlights positive attitudes of healthcare professionals toward promoting physical activity, as well as persistent barriers that hinder effective implementation. Addressing these barriers requires a comprehensive approach, including tailored support for healthcare professionals and improved organisational and systemic structures. Further research is needed to evaluate the effectiveness of strategies aimed at overcoming these obstacles and enhancing physical activity promotion.